The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ceat.201000378
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Alkali, Switchgrass, and Extruder Parameters for Maximum Sugar Recovery

Abstract: The US Department of Energy wants to replace 30 % of transportation fossil fuel with biofuel by 2025. A viable biomass pretreatment method might be found through extrusion. Extrusion pretreatments show a significant improvement on sugar recovery from different biomass feedstocks. However, glucose and combined sugar recovery from extrusion pretreated switchgrass was less than 50 %. Extrusion combined with other pretreatment methods could improve sugar recovery from switchgrass. Low-concentration alkali acts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…No glycerol was found in any of the pretreatment combinations in contrary to the results reported by Karunanithy and Muthukumarappan (Karunanithy & Muthukumarappan, 2010c, 2011a, 2011b, 2011c, 2010a, 2010b.In addition, no furfural and HMF were found in any of the pretreated corn stover samples. The possible reason could be short residence time and no acidic conditions during pretreatment as compared most of the pretreatment methods listed in the table.…”
Section: Byproducts Formationcontrasting
confidence: 83%
See 3 more Smart Citations
“…No glycerol was found in any of the pretreatment combinations in contrary to the results reported by Karunanithy and Muthukumarappan (Karunanithy & Muthukumarappan, 2010c, 2011a, 2011b, 2011c, 2010a, 2010b.In addition, no furfural and HMF were found in any of the pretreated corn stover samples. The possible reason could be short residence time and no acidic conditions during pretreatment as compared most of the pretreatment methods listed in the table.…”
Section: Byproducts Formationcontrasting
confidence: 83%
“…These pretreatment conditions differed from the maximum sugar recovery conditions (180°C, 155 rpm, 20% moisture content, and 8 mm) reported by Karunanithy and Muthukumarappan (2011b). These authors reported a glucose, xylose, and combined sugar recovery of 88, 90, and 90%, respectively, for optimum pretreated corn stover with only extrusion.…”
Section: Comparison Of Alkali Soaking-extrusion Results With Other Prmentioning
confidence: 63%
See 2 more Smart Citations
“…Continuous pretreatment approaches such as screw extrusion have been shown to satisfy the criteria mentioned above (Lin et al, 2012;Karunanithy and Muthukumarappan, 2011a). Extrusion is a well-known process used in food industry and plastic production, which provides high level of shearing and homogenization, and rapid heat transfer, resulting in physiochemical transformations of the treated materials (Miller and Hester, 2007).…”
Section: Introductionmentioning
confidence: 99%